SOME TRANSITION METAL COMPLEXES WITH A NEW TETRADENDATE LIGAND BIS [4-PHENYL 2-DIPROPYL AMINO METHYL 1, 2, 4 -TRIAZOLE 3-THION-5 YL] METHANE - Alias, M F; Ibrahim, S KH; Hassan, S S (Al-Nahrain Journal of Science, 2009)
The ligand bis[4-phenyl 2-diporpyl amino methyl 1,2,4-triazole 3-thion-5 yl] methane and its metal complexes, Ni(П), Zn(П), Hg(П), were synthesized. The prepared complexes were identified and their structural geometries were suggested by using flame atomic absorption technique ,FT-IR and Uv-Vis spectrophotometry in addition to magnetic susceptibility and conductivity measurements .The stoichiometry of the complexes formed in ethanol solution were determined using ,the mole ratio method, gave result which were compared successfully with those obtained from isolated solid state studied.Structural geometries of compounds were also suggested in gas phase by using theoretical treatments via HyperChem-6 program for the molecular mechanics and semi-empirical calculations .The heat of formation ( ) and binding energy ( ) for the free ligand and its metal complexes were calculated by PM3to evaluate the vibration spectra of mannich base and to compare the theoretically calculated wave numbers with experimental values by using (4-phenyl-1,2,4-triazole-5 yl) methane as authentic compound .The theoretically obtained frequencies agreed calculation helped to assign unambiguously the most diagnostic bands.